Effects of Minimum Wages on the Level and Age Composition of Youth Employment - Welch, Finis; Cunningham, James (The Review of Economics and Statistics, 1978)
This paper (1) presents estimates of minimum wage effects on employment of teenagers 14-15, 16-17 and 18-19 years, and (2) decomposes these estimates into scale and substitution components for calculating effects of differential minima. In 1972 the House of Representatives approved an amendment to the Fair Labor Standards Act calling for a youth differential, but one was not included in the Senate version. These bills died when the House refused to submit to conference. In 1973 the Administration proposed another amendment containing a youth differential, but the amendment passed by Congress later that year eliminated it. Although attempts to enact a youth differential have failed,it is clear that support for these measures comes from a consensus concerning the relatively adverse effects of existing minima on teenage employment. It is also likely that the question of differential minima is not dead and it would be nice to have estimates of what effects might be if a differential were enacted. The point of departure for all minimum wage studies has been that those most adversely affected are those who in the absence of the minimum would have earned the lowest wage. In comparing teenagers to adults, there is fairly consistent evidence that minimum wages reduce teenage-adult employment ratios.' But there is less evidence among groups of teenagers themselves. The Labor Department Survey (1970) contrasted males and females, white and non-white, for employment of those 16-17 and for those 18-19. Results are mixed. For white males, estimates conform to expectations of more adverse employment effects for younger workers, but results for white females are inconclusive and there is no relationship for non-white teenagers. Jacob Mincer (1976) and Nori Hashimoto and Mincer (1970) combine all ages 16-19 into one group but distinguish whites from non-whites and find more adverse effects for non-whites. Similarly, Marvin Kosters and Finis Welch (1972) treat ages 16-19 as a single class and distinguish employment by sex and race. More adverse effects are reported for non-whites than for whites and for females than for males. Each of these studies uses time series estimates of teenage employment from Current Population Surveys. These data contain large sampling errors especially for age, sex, and race partitions.2 Students and part-time workers are not distinguished, wages are not available and because the data are for national aggregates, state minimum wage laws are ignored. Here, the data are from the 1 in 100 Public Use Sample of the 1970 Census and refer to teenage employment in the week before the Census was taken. Individual observations are aggregated to state totals. Nationally, students account for half of total teen employment but only one-third of hours worked and females work 95% as many hours as males. Aggregation weights reflect these differences in hours worked. The Census does not contain reliable wage information, and as is true of all previous studies, there is a problem in estimating legislative effects on costs of teenage employment. Cross-state observations enable us to include state wage laws in our estimates of these costs. Section II describes our procedure for inferring legislative effects on teenage employment costs and provides estimates of associated changes in employment. Section III provides empirical results for a decomposition of estimated effects into scale and substitution components and gives estimated effects of a 20% youth differential extended first to those 14-15 and then to those 14-17 year old. A summary follows. Received for publication July 2, 1976. Revision accepted for publication March 4, 1977. * University of California, Los Angeles, and The Rand Corporation. We are grateful to Ernst Stromsdorfer for suggesting this topic and Dennis DeTray and James P. Smith for their helpful comments. Support for this project was provided by a contract from ASPER/USDOL. 'See, for example, the paper by Mincer (1976) and the Labor Department Survey (1970). 2See Welch (1974), the comment by Siskind (1977) and reply by Welch (1977) for discussions of some of the peculiarities of these data.